Electricity Interconnection and Trade between Norway and Russia - das Neves, Maria Madalena (Arctic Review on Law and Politics, 2017)
Anticipated industrial growth in northern Norway, particularly of energy intensive industries such as hydrocarbons and mining, will inevitably result in increased electricity consumption. Northern Norway faces security of supply challenges, and substantial investments are needed in generation, transmission and distribution capacity in order to meet the growing electricity demand. This makes it advantageous to reinforce the existing cross-border electricity infrastructure and trade between Norway and Russia. Cross-border interconnections however are complex, and the controversial debate over Norway’s position on nuclear power in the Kola Peninsula has created public and political opposition that could permanently hinder interconnection expansion plans. This article provides an outline of the existing electricity interconnection and trade between Norway and Russia and examines the potential for reinforcing those arrangements, as well as the concomitant social, political and legal challenges. It argues that in spite of nuclear power controversies, there is still room for expanding the existing interconnection and electricity trade in view of opportunities for the development of other renewable resources in Russia.